2022
DOI: 10.1155/2022/5031202
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 Vaccine Acceptance and Uptake among Healthcare Workers in Trinidad and Tobago

Abstract: Background. COVID-19 vaccine acceptance is important in ensuring the widespread vaccination of the population to achieve herd immunity. Establishing the acceptance of vaccines among healthcare workers, who play a vital role in an immunization program’s success, is important. The aim of this study was to assess the influence of social trust and demographic factors on COVID-19 vaccine acceptance among healthcare workers. Methods. A cross-sectional survey utilizing an electronic questionnaire inquiring about COVI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…A study investigating the acceptance of the vaccine among healthcare workers in Trinidad and Tobago found that age, profession and trust in international public health organizations and other healthcare professionals predict their vaccine uptake 15 . Researchers in Trinidad and Tobago also reported on the safety of the COVID-19 vaccine by examining the side-effects of the ChAdOx1 nCov-19 (Oxford, AstraZeneca COVID-19 vaccine) among healthcare workers 16 .…”
Section: Introductionmentioning
confidence: 99%
“…A study investigating the acceptance of the vaccine among healthcare workers in Trinidad and Tobago found that age, profession and trust in international public health organizations and other healthcare professionals predict their vaccine uptake 15 . Researchers in Trinidad and Tobago also reported on the safety of the COVID-19 vaccine by examining the side-effects of the ChAdOx1 nCov-19 (Oxford, AstraZeneca COVID-19 vaccine) among healthcare workers 16 .…”
Section: Introductionmentioning
confidence: 99%
“…This higher value could have been due to the fact that the study was among the selected categories of front-line health workers implementing the first phase of COVID-19 vaccination and who perhaps were not representative of the entire population/categories of health workers in Nigeria. Similarly, higher values were reported by these foreign studies: 88.0% vaccinated by October 2021 in Trinidad and Tobago,9 and 82.5% vaccinated by May 2021 in Malawi 10. These higher values could be attributed to the fact that the Trinidad and Tobago study was only online and among priority front-line implementers of the vaccination and the Malawi study was among exclusive group of health workers who had been offered the vaccination in their health facilities.…”
Section: Discussionmentioning
confidence: 60%
“…In addition, the assessment of hesitancy to COVID-19 vaccination in these studies were based on different concepts which in most instances did not reflect the definition of hesitancy by the Strategic Advisory Group of Experts on Immunisation (SAGE) Working Group on vaccine hesitancy—delay in receiving or refusal of COVID-19 vaccination despite its availability 6. Few studies were identified to have assessed the uptake of actual vaccines most of which were during the early stages of COVID-19 vaccination when the vaccination was less available and accessible to the entire population or categories of health workers 7–12…”
Section: Introductionmentioning
confidence: 99%
“…Only few studies have assessed the uptake of actual COVID-19 vaccination among the general adult population55 74 75 and among health workers76–79 but most were among subpopulations and when the vaccination was still relatively less available and accessible.…”
Section: Introductionmentioning
confidence: 99%